A method for preparing silicon carbide ceramic from silicon carbide production waste and silicon carbide ceramic
Patent Information
- Application Number
- CN202411233470.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-09-04
AI Technical Summary
[0007]现有技术中公开的利用碳化硅生产废料制备碳化硅陶瓷的方法都有一定的缺陷,存在着制备得到的碳化硅陶瓷的紧密性不足、硬度有待进一步提高
[0086] The method provided by this invention utilizes waste materials from the production of silicon carbide crystals to prepare silicon carbide ceramics, achieving cost savings, waste recycling, and environmental protection. The method uses sodium styrene sulfonate, acrylic monomers, and allyl polyether as raw materials. A modifier is prepared under the action of a persulfate initiator. This modifier is then used to surface-modify silicon carbide powder, reducing the aggregation of the modified silicon carbide powder during ceramic preparation and improving its dispersion. Ultimately, a modified silicon carbide slurry with low viscosity and good dispersion is obtained, resulting in silicon carbide ceramics with high density and high hardness.
Smart Images

Figure BDA0005027003570000191
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silicon carbide technology, and relates to a method for preparing silicon carbide ceramics from silicon carbide production waste, and more particularly to a method for preparing silicon carbide ceramics from silicon carbide production waste and silicon carbide ceramics. Background Technology
[0002] Multi-wire cutting is one of the more commonly used methods for cutting silicon carbide crystals. During the cutting process, steel wires containing diamond particles are used to cut the crystal. Inevitably, there will be losses during the cutting process, with the cut silicon carbide powder and diamond precipitating together in water, resulting in waste liquid containing silicon carbide powder and diamond particles. Furthermore, silicon carbide wafers may crack during the cutting and grinding process, forming silicon carbide wafer waste. This waste is generally disposed of as waste, causing significant waste. Additionally, some unused silicon carbide powder is generated during the silicon carbide crystal growth process, also leading to resource waste.
[0003] In order to enhance the recycling of silicon carbide crystal waste, those skilled in the art have used silicon carbide powder to prepare silicon carbide ceramics.
[0004] CN112851356A discloses a method for preparing silicon carbide ceramics using waste liquid from silicon carbide crystal diamond wire cutting. In this method, silicon carbide powder and diamond particles in the waste liquid from silicon carbide crystal diamond wire cutting are cleaned and dried. Then, single crystal silicon powder is added to the mixed particles, and silicon carbide is produced by reacting the diamond particles in the mixed particles under heating conditions to obtain silicon carbide blanks. Finally, silicon carbide ceramics are produced by firing.
[0005] CN102229499A discloses a method for preparing composite antistatic and wear-resistant ceramics using silicon carbide / silicon micropowder discarded after wire cutting of solar silicon wafers. In this method, acrylate monomers and silicon carbide powder are reacted with an initiator to form a copolymer resin to prepare antistatic ceramics.
[0006] CN103086721A discloses a method for preparing silicon carbide ceramics using silicon carbide solid waste. The method uses pretreated silicon wafer cutting waste slurry as raw material: the silicon wafer cutting waste slurry is pretreated, and the solid waste is used as raw material; polycarbosilane is added as a sintering aid, and the mixture is placed in a polyurethane ball mill jar with anhydrous ethanol as the liquid medium and glycerol as a binder, and then ball-milled using high-purity alumina grinding balls; the solvent is removed by heating; the mixture is pulverized and sieved to obtain silicon carbide powder coated with polycarbosilane; the powder is pressed into preforms of various shapes under high pressure; the preforms are heated from room temperature to 1000℃ over 50 minutes, then heated to 1200℃ at a rate of 10℃ / min, held at that temperature for 60 minutes, and then cooled in the furnace to obtain sintered silicon carbide ceramic products.
[0007] Existing methods for preparing silicon carbide ceramics using silicon carbide production waste all have certain drawbacks, including insufficient density and the need for further improvement in hardness. Therefore, it is crucial to develop a novel method for preparing silicon carbide ceramics from silicon carbide production waste and to develop a new type of silicon carbide ceramic. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing silicon carbide ceramics from silicon carbide production waste, and the silicon carbide ceramics themselves. The method provided by the present invention utilizes silicon carbide crystal production waste to prepare silicon carbide ceramics, achieving cost savings, waste recycling, and environmental protection. The method uses sodium styrene sulfonate, acrylic monomers, and allyl polyether as raw materials, and prepares a modifier under the action of a persulfate initiator. The obtained modifier is used to surface-modify silicon carbide powder, reducing the aggregation of the modified silicon carbide powder during ceramic preparation and improving the dispersion effect of the modified silicon carbide powder. Ultimately, a modified silicon carbide slurry with low viscosity and good dispersion is obtained, resulting in silicon carbide ceramics with high density and high hardness.
[0009] To achieve this objective, the present invention adopts the following technical solution:
[0010] In a first aspect, the present invention provides a method for preparing silicon carbide ceramics from silicon carbide production waste, the method comprising:
[0011] (1) Pre-treatment of silicon carbide production waste to obtain silicon carbide powder;
[0012] (2) Mix sulfonates containing polymerizable double bonds, acrylic monomers, allyl polyethers, persulfates, sulfites and a first solvent to obtain a modifier;
[0013] (3) Modify the silicon carbide powder obtained in step (1) with the modifier obtained in step (2) to obtain modified silicon carbide powder, and prepare silicon carbide ceramics with the obtained modified silicon carbide powder.
[0014] There is no specific order between steps (1) and (2).
[0015] In step (2) of this invention, under the action of the initiator persulfate and the regulator sulfite, the double bonds in sodium styrene sulfonate, acrylic monomer and allyl polyether generate free radicals in the first solvent and complete the free radical polymerization reaction.
[0016] The sulfonates containing polymerizable double bonds described in this invention can improve the dispersion performance of silicon carbide powder, thereby enabling the modified silicon carbide powder to exhibit better dispersion effect in the process of preparing silicon carbide ceramics; in addition, the double bonds in the sulfonates containing polymerizable double bonds can also undergo polymerization reactions with sodium ethylene sulfonate and acrylic acid monomers.
[0017] The acrylic monomers described in this invention undergo polymerization during the preparation of the modifier. After polymerization, they possess certain defoaming and degassing properties. When preparing silicon carbide ceramics using modified silicon carbide powder, they can further eliminate air bubbles in the slurry, forming a uniform and compact preform, thereby obtaining high-hardness silicon carbide ceramics.
[0018] The allyl polyether described in this invention contains hydroxyl groups at its ends. During the modification of silicon carbide powder, it can be linked to the silanol groups on the surface of silicon carbide powder through hydrogen bonding, thereby modifying the silicon carbide powder. At the same time, the allyl polyether also has polyoxyethylene ether segments of a certain length, which can effectively separate the silicon carbide powder, thereby further improving the dispersibility of the modified silicon carbide powder in the preparation of silicon carbide ceramics.
[0019] The persulfate described in this invention is an initiator in the reaction process, and the persulfate provides free radicals to initiate the reaction.
[0020] The sulfite described in this invention has reducing properties. Sodium bisulfite can not only adjust the concentration of free radicals in the obtained modifier, but also play an antioxidant role and promote the degree of free radical polymer reaction, thereby making the modified silicon carbide powder exhibit better dispersion effect in the preparation of silicon carbide ceramics.
[0021] The method provided by this invention utilizes waste materials from the production of silicon carbide crystals to prepare silicon carbide ceramics, achieving cost savings, waste recycling, and environmental protection. The method uses sulfonates containing polymerizable double bonds, acrylic monomers, and allyl polyethers as raw materials. A modifier is prepared under the action of a persulfate initiator and a sulfite regulator. This modifier is then used to surface-modify silicon carbide powder, reducing the aggregation of the modified silicon carbide powder during ceramic preparation and improving its dispersion. Ultimately, a modified silicon carbide slurry with low viscosity and good dispersion is obtained, resulting in silicon carbide ceramics with high density and high hardness.
[0022] Preferably, the silicon carbide production waste in step (1) includes waste liquid generated during silicon carbide crystal cutting, silicon carbide crystal shards generated during silicon carbide crystal processing, and silicon carbide powder remaining during silicon carbide crystal growth.
[0023] Preferably, the pretreatment in step (1) includes pretreating the waste liquid generated during silicon carbide crystal cutting, the cracks generated during silicon carbide crystal processing, and the remaining silicon carbide powder during silicon carbide crystal growth to obtain three types of pretreated silicon carbide powder. The three types of pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder.
[0024] Preferably, the pretreatment includes sequentially filtering and acid washing and drying the waste liquid generated during the silicon carbide crystal cutting process to obtain mixed particles of silicon carbide and diamond; then adding monocrystalline silicon powder to the obtained mixed particles, and then heating to allow the monocrystalline silicon powder to react with the diamond in the mixed particles to generate silicon carbide.
[0025] Preferably, the molar amount of the single-crystal silicon powder added is the same as the molar amount of diamond in the mixed particles; the diamond content in the mixed particles is determined by infrared spectroscopy and / or Raman spectroscopy, and the molar amount of diamond in the mixed particles is calculated based on the diamond content.
[0026] Preferably, the pretreatment includes crushing the fragments generated during the processing of silicon carbide crystals.
[0027] Preferably, the pretreatment includes sequentially calcining, acid washing, and alkali washing of the silicon carbide powder remaining during the silicon carbide crystal growth process.
[0028] The roasting described in this invention is used to remove elemental carbon. The roasting temperature is 2000-2200℃ and the time is 2-6 hours.
[0029] The roasting temperature described in this invention is 2000 to 2200°C, for example, it can be 2000°C, 2020°C, 2040°C, 2060°C, 2080°C, 2100°C, 2120°C, 2140°C, 2160°C, 2180°C or 2200°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0030] The roasting time described in this invention is 2 to 6 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0031] The pickling described in this invention is used to remove trace elements. The acid used for pickling includes any one or at least two of nitric acid, hydrochloric acid, hydrofluoric acid, or sulfuric acid. Typical but non-limiting combinations include the combination of nitric acid and hydrochloric acid, the combination of hydrochloric acid and hydrofluoric acid, the combination of hydrofluoric acid and sulfuric acid, or the combination of nitric acid, hydrochloric acid, and hydrofluoric acid.
[0032] The purpose of alkaline washing in this invention is to remove elemental silicon. The reagents used in alkaline washing include any one or a combination of at least two of sodium hydroxide, potassium hydroxide, sodium carbonate, or potassium carbonate. Typical but non-limiting combinations include combinations of sodium hydroxide and potassium hydroxide, combinations of potassium hydroxide and sodium carbonate, combinations of sodium carbonate and potassium carbonate, or combinations of sodium hydroxide, potassium hydroxide, and sodium carbonate.
[0033] Preferably, the average particle size of the silicon carbide powder obtained in step (1) is less than 200 μm, for example, it can be 199 μm, 190 μm, 180 μm, 170 μm, 160 μm, 150 μm, 140 μm, 130 μm, 120 μm, 110 μm, 100 μm, 90 μm, 80 μm, 70 μm, 60 μm, 50 μm, 40 μm, 30 μm, 20 μm or 10 μm, but is not limited to the listed values. Other unlisted values within this range are also applicable, preferably less than 50 μm.
[0034] Preferably, the mixing in step (2) includes: first mixing a sulfonate containing polymerizable double bonds, a sulfite, and a first solvent to obtain a first mixture; second mixing an acrylic monomer and an allyl polyether to obtain a second mixture; third mixing a persulfate and a first solvent to obtain a third mixture; and then fourth mixing the first mixture, the second mixture, and the third mixture, adjusting the pH, and drying to obtain a modifier.
[0035] Preferably, the fourth mixing includes: adding the second mixture and the third mixture to the first mixture at a constant flow rate at 60-100°C, keeping it at the temperature after addition, and then cooling it to 15-30°C.
[0036] In this invention, the fourth mixing involves adding the second and third mixtures to the first mixture at a constant flow rate at a temperature of 60–100°C. For example, the temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, or 100°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0037] Preferably, the constant flow rate is 0.1 to 1 ml / min, for example, it can be 0.1 ml / min, 0.2 ml / min, 0.3 ml / min, 0.4 ml / min, 0.5 ml / min, 0.6 ml / min, 0.7 ml / min, 0.8 ml / min, 0.9 ml / min or 1 ml / min, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0038] Preferably, the heat preservation time is 1 to 3 hours, for example, it can be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours or 3 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0039] Preferably, the pH adjustment is to adjust the pH to 7-8, for example, 7, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0040] Preferably, the reagent used to adjust the pH is an alkali.
[0041] Preferably, the drying method includes spray drying.
[0042] Preferably, by weight, the sodium styrene sulfonate in step (2) contains 90-110 parts by weight, the sulfite contains 0.21-2.3 parts by weight, the acrylic monomer contains 100-300 parts by weight, the allyl polyether contains 20-50 parts by weight, and the persulfate contains 0.42-4.6 parts by weight.
[0043] In this invention, the amount of sodium styrene sulfonate in the mixing process described in step (2) is 90 to 110 parts by weight, for example, 90, 92, 94, 96, 98, 100, 102, 104, 106, 108 or 110 parts, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0044] In this invention, the amount of sulfite in the mixing process described in step (2) is 0.21 to 2.3 parts by weight, for example, it can be 0.21 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.1 parts or 2.3 parts, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0045] In this invention, the acrylic monomer in the mixing process described in step (2) is 100 to 300 parts by weight, for example, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280 or 300 parts by weight, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0046] In this invention, the weight of allyl polyether in the mixing process described in step (2) is 20 to 50 parts, for example, 20, 22, 25, 27, 30, 32, 35, 37, 40, 42, 45, 48 or 50 parts, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0047] In this invention, the persulfate in the mixing process described in step (2) is 0.42 to 4.6 parts by weight, for example, 0.42, 0.6, 0.8, 1, 1.2, 1.5, 1.7, 2, 2.3, 2.5, 2.7, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.4 or 4.6 parts, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0048] In this invention, the weight of the first solvent in step (2) is not limited by weight, and the amount of the first solvent is sufficient to meet the requirements for the polymerization reaction.
[0049] Preferably, the sulfonate containing polymerizable double bonds includes any one or at least two combinations of sodium styrene sulfonate, sodium acrylate sulfonate, sodium methacrylate sulfonate, sodium 2-acrylamide-2-methylpropanesulfonate, or sodium maleic anhydride sulfonate. Typical but non-limiting combinations include the combination of sodium styrene sulfonate and sodium acrylate sulfonate, the combination of sodium methacrylate sulfonate and sodium 2-acrylamide-2-methylpropanesulfonate, the combination of sodium styrene sulfonate and sodium maleic anhydride sulfonate, or the combination of sodium styrene sulfonate, sodium acrylate sulfonate, and sodium methacrylate sulfonate, preferably sodium styrene sulfonate.
[0050] Preferably, the acrylic monomer comprises any one or a combination of at least two of acrylic acid, methacrylic acid, methyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, or isooctyl acrylate, preferably a combination of hydroxyethyl acrylate and isooctyl acrylate. Typical but non-limiting combinations include combinations of acrylic acid and methacrylic acid, combinations of methyl methacrylate and hydroxyethyl acrylate, combinations of hydroxypropyl acrylate and hydroxybutyl acrylate, combinations of hydroxybutyl acrylate and isooctyl acrylate, or combinations of methacrylic acid, methyl methacrylate, and hydroxyethyl acrylate.
[0051] Preferably, the persulfate includes any one or a combination of at least two of potassium persulfate, ammonium persulfate, or sodium persulfate. Typical but non-limiting combinations include a combination of potassium sulfate and ammonium persulfate, a combination of ammonium persulfate and sodium persulfate, or a combination of potassium persulfate, ammonium persulfate, and sodium persulfate.
[0052] Preferably, the sulfite includes any one or a combination of at least two of sodium sulfite, sodium bisulfite, potassium sulfite, or calcium sulfite. Typical but non-limiting combinations include a combination of sodium sulfite and sodium bisulfite, a combination of potassium sulfite and calcium sulfite, or a combination of sodium sulfite, sodium bisulfite, and potassium sulfite, preferably sodium bisulfite.
[0053] Preferably, the molecular formula of the allyl polyether is CH2CHCH2(C2H4O). m H; where m is 2 to 10, for example, it can be 2, 3, 4, 5, 6, 7, 8, 9 or 10, but is not limited to the listed values. Other unlisted values within this range are also applicable, preferably 6 to 10.
[0054] Preferably, the first solvent includes any one or at least two combinations of water, ethanol, or isopropanol. Typical but non-limiting combinations include a combination of water and ethanol, a combination of ethanol and isopropanol, or a combination of water, ethanol, and isopropanol.
[0055] Preferably, the modification treatment in step (3) includes:
[0056] After mixing the silicon carbide powder obtained in step (1) with the second solvent, the pH is adjusted to obtain a preliminary mixture. The preliminary mixture is then mixed with the modifier obtained in step (2), heated to the final temperature, and stirred while maintaining the temperature. After solid-liquid separation, modified silicon carbide powder is obtained.
[0057] Preferably, the mass ratio of the silicon carbide powder to the second solvent is (30-50):100, for example, it can be 30:100, 32:100, 35:100, 37:100, 40:100, 42:100, 45:100, 47:100 or 50:100, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0058] Preferably, the second solvent comprises any one or at least two combinations of water, ethanol, or isopropanol. Typical but non-limiting combinations include combinations of water and ethanol, combinations of ethanol and isopropanol, or combinations of water, ethanol, and isopropanol.
[0059] Preferably, the mass ratio of the initial mixture to the modifier is 100:(0.5-1), for example, it can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0060] Preferably, the pH adjustment is performed to a value of 9 to 10, such as 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0061] Preferably, the endpoint temperature is 60-80°C, for example, it can be 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C or 80°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0062] Preferably, the stirring time is 0.5 to 1 hour, for example, it can be 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours or 1 hour, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0063] Preferably, the solid-liquid separation method includes filtration.
[0064] Preferably, step (3) involves preparing silicon carbide ceramics from the obtained modified silicon carbide powder, including:
[0065] The modified silicon carbide powder, surfactant, and defoamer are mixed to obtain a ceramic slurry. The obtained ceramic slurry is then sintered to form silicon carbide ceramics.
[0066] Preferably, the mass ratio of the modified silicon carbide powder, surfactant, and defoamer is 100:(0.5-1):(0.5-1).
[0067] The mass ratio of modified silicon carbide powder to surfactant in this invention is 100:(0.5-1), for example, it can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0068] The mass ratio of modified silicon carbide powder to defoamer in this invention is 100:(0.5-1), for example, it can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0069] Preferably, the surfactant comprises any one or a combination of at least two of sodium dodecyl sulfate, sodium dodecyl sulfonate, or sodium dodecylbenzene sulfonate. Typical but non-limiting combinations include a combination of sodium dodecyl sulfate and sodium dodecyl sulfonate, a combination of sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate, or a combination of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.
[0070] Preferably, the defoamer includes any one or a combination of at least two of polyether defoamers, mineral oil defoamers, or silicone defoamers. Typical but non-limiting combinations include a combination of polyether defoamer and mineral oil defoamer, a combination of mineral oil defoamer and silicone defoamer, or a combination of polyether defoamer, mineral oil defoamer, and silicone defoamer.
[0071] Preferably, the sintering process includes: injecting the obtained ceramic slurry into a mold, then sequentially vibrating and vacuuming to remove foam, and then performing sintering.
[0072] Preferably, the sintering treatment is performed at a temperature of 2000–2400°C for 2–6 hours.
[0073] The sintering temperature described in this invention is 2000 to 2400°C, for example, 2000°C, 2050°C, 2100°C, 2150°C, 2200°C, 2250°C, 2300°C, 2350°C or 2400°C, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0074] The sintering time described in this invention is 2 to 6 hours, for example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0075] As a preferred embodiment of the method described in this invention, the method includes:
[0076] (1) The waste liquid generated during the silicon carbide crystal cutting process is sequentially filtered and acid-washed and dried to obtain mixed particles of silicon carbide and diamond; then, monocrystalline silicon powder is added to the obtained mixed particles, and then heated to react the monocrystalline silicon powder with the diamond in the mixed particles to generate silicon carbide, thus obtaining the first pretreated silicon carbide powder.
[0077] The flakes generated during the processing of silicon carbide crystals are crushed to obtain second pretreated silicon carbide powder;
[0078] The silicon carbide powder remaining during the silicon carbide crystal growth process was sequentially calcined, acid-washed, and alkali-washed to obtain the third pretreated silicon carbide powder.
[0079] The first pretreated silicon carbide powder, the second pretreated silicon carbide powder, and the third pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder with an average particle size of less than 50 μm.
[0080] (2) By weight, the first mixture consists of 90-110 parts of a polymerizable double bond sulfonate, 0.21-2.3 parts of a sulfite, and 500-900 parts of a first solvent to obtain a first mixture; the second mixture consists of 100-300 parts of an acrylic monomer and 20-50 parts of an allyl polyether to obtain a second mixture; the third mixture consists of 0.42-4.6 parts of a persulfate and 50-100 parts of the first solvent to obtain a third mixture; then, at 60-100°C, the second mixture and the third mixture are added to the first mixture at a constant flow rate of 0.1-1 ml / min. After the addition is completed, the mixture is kept at this temperature for 1-3 hours, then cooled to 15-30°C, the pH is adjusted to 7-8, and then spray-dried to obtain a modifier;
[0081] (3) The silicon carbide powder obtained in step (1) with a mass ratio of (30-50):100 is mixed with the second solvent and the pH is adjusted to 9-10 to obtain a preliminary mixture. The preliminary mixture with a mass ratio of 100:(0.5-1) is then mixed with the modifier obtained in step (2), heated to 60-80℃ and stirred for 0.5-1h. After filtration, modified silicon carbide powder is obtained.
[0082] The modified silicon carbide powder, surfactant, and defoamer are mixed in a mass ratio of 100:(0.5~1):(0.5~1) to obtain a ceramic slurry. The obtained ceramic slurry is injected into a mold, and then vibration and vacuum suction are performed in sequence to remove foam. Then, it is sintered at 2000~2400℃ for 2~6 hours to obtain silicon carbide ceramic.
[0083] There is no specific order between steps (1) and (2).
[0084] In a second aspect, the present invention provides a silicon carbide ceramic, which is obtained by the method described in the first aspect.
[0085] Compared with the prior art, the present invention has the following beneficial effects:
[0086] The method provided by this invention utilizes waste materials from the production of silicon carbide crystals to prepare silicon carbide ceramics, achieving cost savings, waste recycling, and environmental protection. The method uses sodium styrene sulfonate, acrylic monomers, and allyl polyether as raw materials. A modifier is prepared under the action of a persulfate initiator. This modifier is then used to surface-modify silicon carbide powder, reducing the aggregation of the modified silicon carbide powder during ceramic preparation and improving its dispersion. Ultimately, a modified silicon carbide slurry with low viscosity and good dispersion is obtained, resulting in silicon carbide ceramics with high density and high hardness. Detailed Implementation
[0087] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0088] Example 1
[0089] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste, the method comprising:
[0090] (1) The waste liquid generated during the silicon carbide crystal cutting process is sequentially filtered and acid-washed and dried to obtain mixed particles of silicon carbide and diamond; then, monocrystalline silicon powder is added to the obtained mixed particles, and then heated to react the monocrystalline silicon powder with the diamond in the mixed particles to generate silicon carbide, thus obtaining the first pretreated silicon carbide powder.
[0091] The flakes generated during the processing of silicon carbide crystals are crushed to obtain second pretreated silicon carbide powder;
[0092] The silicon carbide powder remaining during the silicon carbide crystal growth process was sequentially calcined, acid-washed, and alkali-washed to obtain the third pretreated silicon carbide powder.
[0093] The first pretreated silicon carbide powder, the second pretreated silicon carbide powder, and the third pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder with an average particle size of 35 μm.
[0094] (2) By weight, the first mixture consists of 100 parts sodium styrene sulfonate, 1 part sodium bisulfite, and 700 parts water to obtain the first mixture; the second mixture consists of 200 parts acrylic monomer and 35 parts allyl polyether to obtain the second mixture; the third mixture consists of 2 parts sodium persulfate and 75 parts water to obtain the third mixture; then, at 80°C, the second mixture and the third mixture are added to the first mixture at a constant flow rate of 0.5 ml / min. After the addition is completed, the mixture is kept at this temperature for 2 hours, then cooled to 24°C, the pH is adjusted to 7.5, and then spray-dried to obtain the modifier.
[0095] (3) The silicon carbide powder obtained in step (1) with a mass ratio of 40:100 is mixed with water and the pH is adjusted to 9.5 to obtain a preliminary mixture. The preliminary mixture with a mass ratio of 100:0.7 is then mixed with the modifier obtained in step (2), heated to 75°C and stirred for 0.75 hours. After filtration, modified silicon carbide powder is obtained.
[0096] The modified silicon carbide powder, sodium dodecyl sulfate and polyether defoamer were mixed in a mass ratio of 100:0.75:0.75 to obtain a ceramic slurry. The obtained ceramic slurry was injected into a mold, and then vibration and vacuum suction were performed in sequence to remove foam. Finally, it was sintered at 2200℃ for 4 hours to obtain silicon carbide ceramic.
[0097] There is no specific order between steps (1) and (2).
[0098] Example 2
[0099] (1) The waste liquid generated during the silicon carbide crystal cutting process is sequentially filtered and acid-washed and dried to obtain mixed particles of silicon carbide and diamond; then, monocrystalline silicon powder is added to the obtained mixed particles, and then heated to react the monocrystalline silicon powder with the diamond in the mixed particles to generate silicon carbide, thus obtaining the first pretreated silicon carbide powder.
[0100] The flakes generated during the processing of silicon carbide crystals are crushed to obtain second pretreated silicon carbide powder;
[0101] The silicon carbide powder remaining during the silicon carbide crystal growth process was sequentially calcined, acid-washed, and alkali-washed to obtain the third pretreated silicon carbide powder.
[0102] The first pretreated silicon carbide powder, the second pretreated silicon carbide powder, and the third pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder with an average particle size of 20 μm.
[0103] (2) By weight, the first mixture consists of 90 parts sodium acrylate sulfonate, 0.21 parts sodium sulfite, and 500 parts water to obtain the first mixture; the second mixture consists of 100 parts acrylic acid monomer and 20 parts allyl polyether to obtain the second mixture; the third mixture consists of 0.42 parts potassium persulfate and 50 parts ethanol to obtain the third mixture; then, at 60°C, the second mixture and the third mixture are added to the first mixture at a constant flow rate of 1 ml / min. After the addition is completed, the mixture is kept at the temperature for 3 hours, then cooled to 30°C, the pH is adjusted to 7, and then spray-dried to obtain the modifier.
[0104] (3) The silicon carbide powder obtained in step (1) with a mass ratio of 30:100 is mixed with water and the pH is adjusted to 9 to obtain a preliminary mixture. The preliminary mixture with a mass ratio of 100:1 is then mixed with the modifier obtained in step (2), heated to 80°C and stirred for 0.5 hours. After filtration, modified silicon carbide powder is obtained.
[0105] The modified silicon carbide powder, sodium dodecyl sulfonate, and mineral oil defoamer were mixed in a mass ratio of 100:1:0.5 to obtain a ceramic slurry. The obtained ceramic slurry was injected into a mold, and then vibration and vacuum suction were performed in sequence to remove foam. Finally, it was sintered at 2400℃ for 2 hours to obtain silicon carbide ceramic.
[0106] There is no specific order between steps (1) and (2).
[0107] Example 3
[0108] (1) The waste liquid generated during the silicon carbide crystal cutting process is sequentially filtered and acid-washed and dried to obtain mixed particles of silicon carbide and diamond; then, monocrystalline silicon powder is added to the obtained mixed particles, and then heated to react the monocrystalline silicon powder with the diamond in the mixed particles to generate silicon carbide, thus obtaining the first pretreated silicon carbide powder.
[0109] The flakes generated during the processing of silicon carbide crystals are crushed to obtain second pretreated silicon carbide powder;
[0110] The silicon carbide powder remaining during the silicon carbide crystal growth process was sequentially calcined, acid-washed, and alkali-washed to obtain the third pretreated silicon carbide powder.
[0111] The first pretreated silicon carbide powder, the second pretreated silicon carbide powder, and the third pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder with an average particle size of 48 μm.
[0112] (2) By weight, the first mixture consists of 110 parts sodium methacrylate sulfonate, 2.3 parts potassium sulfite, and 900 parts ethanol to obtain a first mixture; the second mixture consists of 300 parts acrylic acid monomer and 50 parts allyl polyether to obtain a second mixture; the third mixture consists of 4.6 parts potassium persulfate and 100 parts water to obtain a third mixture; then, at 100°C, the second mixture and the third mixture are added to the first mixture at a constant flow rate of 0.1 ml / min. After the addition is completed, the mixture is kept at this temperature for 1 hour, then cooled to 15°C, the pH is adjusted to 8, and then spray-dried to obtain the modifier.
[0113] (3) The silicon carbide powder obtained in step (1) with a mass ratio of 50:100 is mixed with ethanol and the pH is adjusted to 10 to obtain a preliminary mixture. The preliminary mixture with a mass ratio of 100:0.5 is then mixed with the modifier obtained in step (2), heated to 60°C and stirred for 1 hour. After filtration, modified silicon carbide powder is obtained.
[0114] The modified silicon carbide powder, sodium dodecylbenzenesulfonate, and organosilicon defoamer were mixed in a mass ratio of 100:0.5:1 to obtain a ceramic slurry. The obtained ceramic slurry was injected into a mold, and then vibration and vacuum suction were performed in sequence to remove foam. Finally, it was sintered at 2000℃ for 6 hours to obtain silicon carbide ceramic.
[0115] There is no specific order between steps (1) and (2).
[0116] Example 4
[0117] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for the average particle size of the silicon carbide powder obtained after grinding in step (1) being 250 μm, the rest is the same as in Example 1.
[0118] Example 5
[0119] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for step (2), in which the second mixture and the third mixture are added to the first mixture at 40°C, the rest is the same as in embodiment 1.
[0120] Example 6
[0121] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for step (2), in which the second mixture and the third mixture are added to the first mixture at 120°C, the rest is the same as in embodiment 1.
[0122] Example 7
[0123] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except that the mass ratio of the initial mixture to the modifier obtained in step (2) is 100:0.2 during remixing in step (3), the rest is the same as in Example 1.
[0124] Example 8
[0125] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except that the mass ratio of the initial mixture to the modifier obtained in step (2) is 100:1.5 during remixing in step (3), the rest is the same as in Example 1.
[0126] Example 9
[0127] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for step (3), which involves mixing and heating to 40°C before stirring, the rest of the method is the same as in Example 1.
[0128] Example 10
[0129] This embodiment provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for step (3), which involves mixing and heating to 100°C before stirring, the rest of the method is the same as in Example 1.
[0130] Comparative Example 1
[0131] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting sodium styrene sulfonate in step (2), the method is the same as in Example 1.
[0132] Comparative Example 2
[0133] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting sodium bisulfite in step (2), the method is the same as in Example 1.
[0134] Comparative Example 3
[0135] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting the acrylic monomer in step (2), the method is the same as in Example 1.
[0136] Comparative Example 4
[0137] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting allyl polyether in step (2), the method is the same as in Example 1.
[0138] Comparative Example 5
[0139] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting sodium persulfate in step (2), the method is the same as in Example 1.
[0140] Comparative Example 6
[0141] This comparative example provides a method for preparing silicon carbide ceramics from silicon carbide production waste. Except for omitting step (2) and step (3), the silicon carbide powder obtained in step (1) with a mass ratio of 40:100 is mixed with a second solvent and the pH is adjusted to 9.5 to obtain a preliminary mixture. Then, the preliminary mixture with a mass ratio of 100:0.7 is mixed with the modifier obtained in step (2), heated to 75°C and stirred for 0.75 hours. After filtration, modified silicon carbide powder is obtained. In other words, silicon carbide ceramics are prepared directly from the silicon carbide powder obtained in step (1). All other aspects are the same as in the example.
[0142] Silicon carbide ceramics were prepared using the method of preparing silicon carbide ceramics from silicon carbide production waste provided in the above embodiments and comparative examples. The dispersibility of the ceramic slurry obtained in step (3) was evaluated, and the compactness and hardness of the silicon carbide ceramics obtained by final sintering were evaluated.
[0143] The evaluation method for the dispersibility of ceramic slurry includes viscosity testing. Good dispersibility of ceramic slurry means good fluidity and correspondingly low viscosity. The viscosity testing method for ceramic slurry is as follows: the viscosity of ceramic slurry is tested using a rheometer, and the test results are shown in Table 1.
[0144] The evaluation method for the dispersibility of ceramic slurry also includes viscosity testing after standing. The smaller the viscosity change of ceramic slurry after standing, the better the dispersibility. The method for testing the viscosity of ceramic slurry after standing for 24 hours is as follows: the viscosity of ceramic slurry is tested again after standing for 24 hours. The test results are shown in Table 1.
[0145] The evaluation method for the compactness of silicon carbide ceramics includes bulk density testing. The higher the bulk density, the higher the compactness. The test method for the bulk density of silicon carbide ceramics is: National Standard GB / T 25995-2010 "Test Method for Density and Apparent Porosity of Fine Ceramics". The test results are shown in Table 1.
[0146] The Vickers hardness test method for the silicon carbide ceramic is as follows: the hardness of the ceramic sample is tested using a Vickers hardness tester, and the test results are shown in Table 1.
[0147] Table 1
[0148]
[0149] From Table 1, we can obtain:
[0150] (1) The silicon carbide ceramics prepared by the methods provided in Examples 1 to 3 of the present invention have high density and hardness;
[0151] (2) By comparing Example 1 and Example 4, it can be seen that the average particle size of the silicon carbide powder obtained after grinding in step (1) of the present invention will affect the performance of the obtained ceramic slurry and silicon carbide ceramic. When the average particle size of the silicon carbide powder is less than 200 μm, the obtained ceramic slurry has a lower viscosity and better dispersion, and the obtained silicon carbide ceramic has excellent performance. This is because when the particle size of the silicon carbide powder is too large, it is easy to agglomerate in the dispersion system, which affects the dispersibility. At the same time, the larger particles have a smaller specific surface area and less interaction with the modifier, resulting in uneven dispersion and affecting the final compactness and hardness of the silicon carbide ceramic.
[0152] (3) By comparing Example 1 with Examples 5 and 6, it can be seen that the temperature at which the second and third mixtures are added to the first mixture in step (2) of the present invention will affect the performance of the obtained ceramic slurry and silicon carbide ceramic. When the temperature is 60 to 100°C, the obtained ceramic slurry has a lower viscosity and better dispersion, and the obtained silicon carbide ceramic has excellent performance. This is because if the reaction temperature is too low during the polymerization reaction, the free radical generation rate will be reduced, and the polymerization effect of the modifier will be reduced. If the reaction temperature is too high, the initiator will decompose too quickly, resulting in a decrease in the utilization rate of the initiator. High temperature may introduce unnecessary side reactions, affecting the final performance of the modifier.
[0153] (4) By comparing Example 1 with Examples 7 and 8, it can be seen that the mass ratio of the initial mixture to the modifier obtained in step (2) during remixing in step (3) of the present invention will affect the performance of the obtained ceramic slurry and silicon carbide ceramic. When the mass ratio of the initial mixture to the modifier is 100:(0.5~1), the obtained ceramic slurry has a lower viscosity and better dispersion, and the obtained silicon carbide ceramic has excellent performance. This is because if the amount of modifier is too small, the surface of the mixture cannot be fully modified, and the dispersion performance will naturally decrease, which will ultimately affect the dispersion of the slurry and the final compactness and hardness of the ceramic. When the amount of modifier is too large, the hydroxyl groups in the modifier structure cannot be connected with the hydroxyl groups on the surface of silicon carbide through hydrogen bonds and consumed. The modifier itself may form hydrogen bonds to form self-agglomeration, which will affect the dispersion performance of the silicon carbide ceramic slurry, and ultimately affect the compactness and hardness of the silicon carbide ceramic.
[0154] (5) By comparing Example 1 with Examples 9 and 10, it can be seen that the final temperature of heating after remixing in step (3) of the present invention will affect the performance of the obtained ceramic slurry and silicon carbide ceramic. When the final temperature of heating is 60-80°C, the obtained ceramic slurry has a lower viscosity and better dispersion, and the obtained silicon carbide ceramic has excellent performance. This is because the temperature of 60-80°C during the modification process is more conducive to the dispersion of silicon carbide powder, so that it can better contact with the modification agent and improve the modification efficiency. On the contrary, the temperature is too low and will affect the modification efficiency. On the other hand, if the reaction temperature is too high, the chemical bonding strength of the modification process will be weakened, which will eventually lead to a weakening of the modification effect of the modifier, thereby affecting the dispersion performance of the silicon carbide ceramic slurry, and ultimately affecting the compactness and hardness of the silicon carbide ceramic.
[0155] (6) By comparing Example 1 with Comparative Example 1, it can be seen that the sodium styrene sulfonate described in this invention can improve the dispersion performance of silicon carbide powder, thereby making the modified silicon carbide powder exhibit better dispersion effect in the process of preparing silicon carbide ceramics.
[0156] (7) By comparing Example 1 and Comparative Example 2, it can be seen that the sodium bisulfite in the present invention has reducing properties. Sodium bisulfite can not only adjust the free radical concentration in the obtained modifier, but also play an antioxidant role, thereby making the modified silicon carbide powder exhibit better dispersion effect in the process of preparing silicon carbide ceramics.
[0157] (8) By comparing Example 1 and Comparative Example 3, it can be seen that the acrylic monomer described in this invention will polymerize during the preparation of the modifier. After polymerization, it has certain defoaming and degassing properties. When preparing silicon carbide ceramics with modified silicon carbide powder, it can further eliminate the bubbles in the slurry and form a uniform and dense preform, thereby obtaining high-hardness silicon carbide ceramics.
[0158] (9) By comparing Example 1 and Comparative Example 4, it can be seen that the allyl polyether in this invention has hydroxyl groups at the end. During the modification of silicon carbide powder, it can be linked with the silanol groups on the surface of silicon carbide powder through hydrogen bonding to modify the silicon carbide powder. At the same time, the allyl polyether also has a certain length of polyoxyethylene ether chain segment, which can effectively separate the silicon carbide powder, thereby further improving the dispersibility of the modified silicon carbide powder in the process of preparing silicon carbide ceramics.
[0159] (10) By comparing Example 1 and Comparative Example 5, it can be seen that the persulfate in the present invention is an initiator in the reaction process. The persulfate provides free radicals to initiate the reaction and obtain a modifier, so that the ceramic slurry prepared by the modified silicon carbide powder has a better dispersion effect, thereby obtaining high hardness silicon carbide ceramics.
[0160] (11) By comparing Example 1 and Comparative Example 6, it can be seen that the method provided by the present invention uses the production waste of silicon carbide crystals to prepare silicon carbide ceramics, which achieves the purpose of saving costs, recycling waste and protecting the environment; the method uses sodium styrene sulfonate, acrylic monomers and allyl polyether as raw materials, and prepares a modifier under the action of persulfate initiator. The obtained modifier is used to modify the surface of silicon carbide powder, which reduces the aggregation of modified silicon carbide powder in the ceramic preparation process, improves the dispersion effect of modified silicon carbide powder, and finally obtains modified silicon carbide slurry with low viscosity and good dispersion, thereby obtaining silicon carbide ceramics with high density and high hardness.
[0161] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing silicon carbide ceramics from silicon carbide production waste, characterized in that, The method includes: (1) Pre-treatment of silicon carbide production waste to obtain silicon carbide powder with an average particle size of less than 200 μm; (2) Mix sulfonates containing polymerizable double bonds, acrylic monomers, allyl polyethers, persulfates, sulfites and the first solvent to obtain a modifier; (3) Modify the silicon carbide powder obtained in step (1) with the modifier obtained in step (2) to obtain modified silicon carbide powder, and prepare silicon carbide ceramics with the obtained modified silicon carbide powder. The mixing in step (2) includes: first mixing sulfonates and sulfites containing polymerizable double bonds with a first solvent to obtain a first mixture; second mixing acrylic monomers and allyl polyethers to obtain a second mixture; third mixing persulfate and the first solvent to obtain a third mixture; and then fourth mixing the first mixture, the second mixture and the third mixture, adjusting the pH and drying to obtain a modifier. The fourth mixing includes: adding the second mixture and the third mixture to the first mixture at a constant flow rate at 60~100℃, keeping it at the temperature after addition, and then cooling it to 15~30℃; The modification process in step (3) includes: After mixing the silicon carbide powder obtained in step (1) with the second solvent, the pH is adjusted to obtain a preliminary mixture. Then, the preliminary mixture with a mass ratio of 100:(0.5~1) and the modifier obtained in step (2) are mixed and heated to 60~80℃. While keeping warm, the mixture is stirred. After solid-liquid separation, modified silicon carbide powder is obtained. There is no specific order between steps (1) and (2).
2. The method according to claim 1, characterized in that, The silicon carbide production waste mentioned in step (1) includes waste liquid generated during silicon carbide crystal cutting, silicon carbide crystal shards generated during silicon carbide crystal processing, and silicon carbide powder remaining during silicon carbide crystal growth.
3. The method according to claim 1, characterized in that, The pretreatment in step (1) includes pretreating the waste liquid generated during the silicon carbide crystal cutting process, the cracks generated during the silicon carbide crystal processing process, and the silicon carbide powder remaining during the silicon carbide crystal growth process to obtain three kinds of pretreated silicon carbide powder. The three kinds of pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder.
4. The method according to claim 1, characterized in that, The average particle size of the silicon carbide powder obtained in step (1) is less than 50 μm.
5. The method according to claim 1, characterized in that, The constant flow rate is 0.1~1 ml / min.
6. The method according to claim 1, characterized in that, The pH adjustment is to adjust the pH to 7-8.
7. The method according to claim 1, characterized in that, The sulfonate containing polymerizable double bonds in step (2) is sodium styrene sulfonate, and by weight, the amount of sodium styrene sulfonate in the mixing process in step (2) is 90-110 parts, the amount of sulfite is 0.21-2.3 parts, the amount of acrylic monomer is 100-300 parts, the amount of allyl polyether is 20-50 parts, and the amount of persulfate is 0.42-4.6 parts.
8. The method according to claim 1, characterized in that, The sulfonate containing polymerizable double bonds includes any one or at least a combination of two of sodium styrene sulfonate, sodium acrylate sulfonate, sodium methacrylate sulfonate, sodium 2-acrylamide-2-methylpropanesulfonate, or sodium maleic anhydride sulfonate.
9. The method according to claim 1, characterized in that, The sulfonate containing polymerizable double bonds is sodium styrene sulfonate.
10. The method according to claim 1, characterized in that, The acrylic monomer includes any one or a combination of at least two of the following: acrylic acid, methacrylic acid, methyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, or isooctyl acrylate.
11. The method according to claim 1, characterized in that, The acrylic monomer is a combination of hydroxyethyl acrylate and isooctyl acrylate.
12. The method according to claim 1, characterized in that, The molecular formula of the allyl polyether is CH2CHCH2(C2H4O). m H; where m is 2~10.
13. The method according to claim 1, characterized in that, The molecular formula of the allyl polyether is CH2CHCH2(C2H4O). m H; where m is 6~10.
14. The method according to claim 1, characterized in that, The mass ratio of silicon carbide powder to the second solvent is (30~50):
100.
15. The method according to claim 1, characterized in that, The pH adjustment is set to 9-10.
16. The method according to claim 1, characterized in that, The stirring time is 0.5~1h.
17. The method according to any one of claims 1 to 16, characterized in that, Step (3) involves preparing silicon carbide ceramics from the obtained modified silicon carbide powder, including: The modified silicon carbide powder, surfactant, and defoamer are mixed to obtain a ceramic slurry. The obtained ceramic slurry is then sintered to form silicon carbide ceramics.
18. The method according to claim 17, characterized in that, The sintering process includes: injecting the obtained ceramic slurry into a mold, then sequentially vibrating and vacuuming to remove foam, and then performing sintering.
19. The method according to claim 18, characterized in that, The sintering process is carried out at a temperature of 2000~2400℃ for 2~6 hours.
20. The method according to claim 1, characterized in that, The method includes: (1) The waste liquid generated during the silicon carbide crystal cutting process is sequentially filtered and acid-washed and dried to obtain mixed particles of silicon carbide and diamond; then, monocrystalline silicon powder is added to the obtained mixed particles, and then heated to react the monocrystalline silicon powder with the diamond in the mixed particles to generate silicon carbide, thus obtaining the first pretreated silicon carbide powder. The flakes generated during the processing of silicon carbide crystals are crushed to obtain second pretreated silicon carbide powder; The silicon carbide powder remaining during the silicon carbide crystal growth process was sequentially calcined, acid-washed, and alkali-washed to obtain the third pretreated silicon carbide powder. The first pretreated silicon carbide powder, the second pretreated silicon carbide powder, and the third pretreated silicon carbide powder are then mixed and ground to obtain silicon carbide powder with an average particle size of less than 50 μm. (2) By weight, the first mixture consists of 90-110 parts of a sulfonate containing polymerizable double bonds, 0.21-2.3 parts of sulfite, and 500-900 parts of a first solvent to obtain a first mixture; the second mixture consists of 100-300 parts of acrylic monomer and 20-50 parts of allyl polyether to obtain a second mixture; the third mixture consists of 0.42-4.6 parts of persulfate and 50-100 parts of the first solvent to obtain a third mixture; then, at 60-100°C, the second mixture and the third mixture are added to the first mixture at a constant flow rate of 0.1-1 ml / min. After the addition is completed, the mixture is kept at the temperature for 1-3 hours, then cooled to 15-30°C, the pH is adjusted to 7-8, and then spray-dried to obtain a modifier; (3) After mixing the silicon carbide powder obtained in step (1) with the second solvent at a mass ratio of (30~50):100, adjust the pH to 9~10 to obtain a preliminary mixture. Then mix the preliminary mixture with the modifier obtained in step (2) at a mass ratio of 100:(0.5~1), heat to 60~80℃ and keep warm while stirring for 0.5~1h. After filtration, obtain modified silicon carbide powder. The modified silicon carbide powder, surfactant, and defoamer are mixed in a mass ratio of 100:(0.5~1):(0.5~1) to obtain a ceramic slurry. The obtained ceramic slurry is injected into a mold, and then vibration and vacuum suction are performed in sequence to remove foam. Finally, it is sintered at 2000~2400℃ for 2~6 hours to obtain silicon carbide ceramic. There is no specific order between steps (1) and (2).
21. A silicon carbide ceramic, characterized in that, The silicon carbide ceramic is obtained by the method described in any one of claims 1 to 20.
Citation Information
Patent Citations
Method for preparing composite anti-static and wear resistant ceramic by using depleted carborundum / silicon powder generated through solar silicon wafer linear cutting
CN102229499A
Method for preparing silicon carbide ceramic from silicon carbide solid waste
CN103086721A
Method for preparing silicon carbide ceramic by utilizing diamond wire cutting waste liquid of silicon carbide crystal
CN112851356A
Preparation method of silicon carbide slurry with high solid content
CN101830704A
Acrylic copolymer dispersing agent with wettability and preparation method thereof
CN117801177A